Pengaruh Model Pembelajaran Guided Inquiry dengan Mind Map terhadap Hasil Belajar dan Motivasi Siswa pada Materi Redoks di Kelas X SMA Negeri 5 Palu - Lumentut, Regina S.; Said, Irwan; Mustapa, Kasmudin (Universitas Tadulako, 2017)
This study aimed to investigate the effect of guided inquiry learning model with mind map toward learning achievement and motivation of students on Reduction-Oxidation in Class X at SMA 5 Palu. This study was a quasi-experimental design with a non-randomized pretest-posttest control group design. This study was carried out by holding two groups of Class X Sciences 1 as the experimental group (n = 31) and Class X Sciences2 as the control group (n = 32). Testing of learning achievement data of students used t-test statistical analysis of two parties with the prerequisite tests: normality and homogeneity tests of written test given after learning (posttest). Results of the data analysis showed the average value (i) of the experimental class was 56.48 with a standard deviation of 11.07, and (ii) of the control class was 46.25 with a standard deviation of 11.98. Based on the hypothesis test results with t-test statistical of two parties obtained -ttable â‰¤ tcounttâ‰¥ + ttable (tcount = 2.43 and ttable= 1.67) with a significance level of Î± = 0.05 and degrees of freedom of 61, then H0 is rejected and Ha is accepted. Results of the data analysis of students motivation by using descriptive statistical analysis from the questionnaire of students motivation showed that the experimental class was currently on attitudes agree with the positive category of 82.58%, and the control class was on attitudes agree with the positive category of 83.78%.It can be concluded that there was an effect of guided inquiry learning model with mind map toward learning achievement of students, but it had no effect on the motivation of students in Class X at SMA 5 Palu on Reduction-Oxidation.